Plastic Pollution and Small Juvenile Marine Turtles: A Potential Evolutionary Trap - Duncan, Emily M.; Broderick, Annette C.; Critchell, Kay; Galloway, Tamara S.; Hamann, Mark; Limpus, Colin J.; Lindeque, Penelope K.; Santillo, David; Tucker, Anton D.; Whiting, Scott; Young, Erina J.; Godley, Brendan J. (Frontiers in Marine Science, 2021)
The ingestion of plastic by marine turtles is now reported for all species. Small juvenile turtles (including post-hatchling and oceanic juveniles) are thought to be most at risk, due to feeding preferences and overlap with areas of high plastic abundance. Their remote and dispersed life stage, however, results in limited access and assessments. Here, stranded and bycaught specimens from Queensland Australia, Pacific Ocean (PO; n=65; 1993-2019) and Western Australia, Indian Ocean (IO; n=56; 2015-2019) provide a unique opportunity to assess the extent of plastic (> 1mm) ingestion in five species (green (Chelonia mydas), loggerhead (Caretta caretta), hawksbill (Eretmochelys imbricata), olive ridley (Lepidochelys olivacea) and flatback turtles (Natator depressus)). In the Pacific Ocean, high incidence of ingestion occurred in green (83%; n=36), loggerhead (86%; n=7), flatback (80%; n=10) and olive ridley turtles (29%; n=7). There was an overall lower incidence in IO; highest being in the flatback (28%; n=18), the loggerhead (21%; n=14) and green (9%; n=22). No macroplastic debris ingestion was documented for hawksbill turtles in either site although sample sizes were smaller for this species (PO n=5; IO n=2). In the Pacific Ocean, the majority of ingested debris was made up of hard fragments (mean of all species 52% species averages 46-97%), whereas for the Indian Ocean these were filamentous plastics (52%; 43-77%). The most abundant colour for both sites across all species was clear (PO: 36%; IO: 39%), followed by white for PO (36%) then green & blue for IO (16%; 16%). The polymers most commonly ingested by turtles in both oceans were polyethylene (PE; PO-58%; IO-39%) and polypropylene (PP; PO-20.2%; IO-23.5%). We frame the high occurrence of ingested plastic present in this marine turtle life stage as a potential evolutionary trap as they undertake their development in what are now some of the most polluted areas of the global oceans.